2012
DOI: 10.1080/02626667.2011.633917
|View full text |Cite
|
Sign up to set email alerts
|

Multi-variable verification of hydrological processes in the upper North Saskatchewan River basin, Alberta, Canada

Abstract: The ACRU agro-hydrological modelling system was set up to simulate the impacts of climate change on the hydrological responses of the 3856-km 2 Cline River watershed, the major headwater of the upper North Saskatchewan River basin in central Alberta, Canada. The physical-conceptual ACRU model was set up to simulate all elements of the hydrological cycle on a daily time step for the 1961-1990 baseline period, to serve as the basis for later climate change impact simulations. After parameterization, the output f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Forbes et al () and Kienzle et al () have reported increased winter runoff, earlier spring freshet, and decreased summer runoff for southwestern Alberta. The same findings were reported for parts of the Rocky Mountains (Rood et al ; Sauchyn and Kulshreshtha ; Nemeth et al ). Correspondingly, regions where snowpack and glacier melt are major sources of the annual streamflow are significantly impacted by climate change (Cayan et al ; Mote ; Hamlet et al ).…”
Section: Introductionsupporting
confidence: 84%
“…Forbes et al () and Kienzle et al () have reported increased winter runoff, earlier spring freshet, and decreased summer runoff for southwestern Alberta. The same findings were reported for parts of the Rocky Mountains (Rood et al ; Sauchyn and Kulshreshtha ; Nemeth et al ). Correspondingly, regions where snowpack and glacier melt are major sources of the annual streamflow are significantly impacted by climate change (Cayan et al ; Mote ; Hamlet et al ).…”
Section: Introductionsupporting
confidence: 84%